Pengembangan Sistem Informasi Pengawasan Operasional Dan Teknis Penambangan (Studi Kasus: PT. United Tractors Site Tanjung) - Dwi Jan Prayogi; Achmad Arwan; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Mining areas are areas that are prone to accidents, so accident prevention measures are important in daily operational and technical mining activities. To decrease the occurrence of accidents in the mining area, a surveillance program called 13 PWS (Pengawasan Wajib Superior) was created. 13 PWS itself consists of, Green Card, General Inspection, PTO/SBO/FLPG, Personal Contact, Safety Talk, JSA, P5M/Check In/FLPG, Major Risk, Inspection LV, Audit APD, Tools/Lifting inspection, HouseKeeping, dan Safety Committee Meeting. In practice, there are many problems with PWS, including manual filling that causes a lot of space to be used to store forms, and the complexity of conducting monthly recapitulations which are used as evaluations in mining operations and techniques, a lot of data loss and many-many more. So, a system is needed to make it easier to fill out forms, store forms, and process data. To answer these challenges, a problem analysis, design, implementation and testing of the monitoring information system was created by applying an object-oriented approach. The process of problem analysis produces an information system specification called a use case diagram. After obtaining the requirements specification, a documentation of the object interaction model is made, namely sequence diagrams, class diagrams, database design, algorithm design, and interface design. After obtaining the design, the system implementation is created based on the design that has been made. After the implementation process is complete, testing is carried out based on the functional and non-functional requirements that have been previously made. Testing yields 100% valid on unit and integration tests. Compatibility testing shows that the system can run on various systems. At the final stage, conclusions and suggestion can be drawn based on the system that has been created.